The world of the Middle Ages : a reorientation of medieval history - La Monte, John Life, 1902-, (Appleton-Century-Crofts, 1949)
1050-1200 -- The apogee of the Middle Ages : the thirteenth century -- The decline of the Medieval world, 1300-1500.